"The Community That Takes Care of Itself": A Feasibility Study to Support Families Caring for a Loved One With Alzheimer Disease. Issue 4 (October 2022) - Gambella, Elena; Valenza, Silvia; Giulietti, Maria Velia; Gagliardi, Cristina; Civerchia, Patrizia; Fabbietti, Paolo; Lattanzio, Fabrizia; Pelliccioni, Giuseppe
Abstract : This pilot project was aimed at supporting those families caring at home for loved ones suffering from Alzheimer dementia. Fourteen dyads of "caregivers-loved ones with dementia" were recruited and assigned either to the experimental group (n = 7) or to the control group (n = 7). The experimental group attended a training course, an Alzheimer Café, a self-help group for caregivers, and the support from a volunteer and professional nurse in-home visits, while the control group's dyads attended a standard intervention. To investigate the effects of this integrated and interprofessional model of care, caregivers completed the Caregiver Burden Inventory and 2 ad hoc structured questions to evaluate whether quality of life of the dyads was changed. Moreover, the caregivers of the experimental group completed the Self-Assessment Single Questionnaire, version 6 (Q-UAV6). Only caregivers of the experimental group reported a significant reduction in burden and an improved quality of life of the dyad. They also showed a greater acceptance of the disease, became experts in the care of their loved ones, and improved their relationship. The creation of a service integration network of professionals, volunteers, and families has been shown to be useful in supporting those families caring at home for loved ones suffering from Alzheimer dementia.